Development of a New Model of Humeral Hemiarthroplasty in Rats. Issue 1 (31st December 2023) - Kazum, Efi; Maman, Eran; Sharfman, Zachary T.; Wengier, Reut; Sher, Osnat; Khoury, Amal; Chechik, Ofir; Dolkart, Oleg
Abstract: Purpose: In vivo models are anatomically comparable to humans allowing to reproduce the patterns and progression of the disease and giving the opportunity to study the symptoms and responses to new treatments and materials. This study aimed to establish a valid and cost-effective in vivo rat model to assess the effects of implanted shoulder hemiarthroplasty materials on glenoid articular cartilage wear. Methods: Eight adult male Wistar rats underwent right shoulder hemi-arthroplasty. A stainless steel metal bearing was used as a shoulder joint prosthesis. X-rays were performed one week after surgery to verify correct implant position. Additional X-rays were performed 30 and 60 days post-implantation. Animals were sacrificed 24 weeks after implantation. All specimens were evaluated with micro-CT for cartilage and bone wear characteristics as well as histologically for signs of osteoarthritis. Samples were compared to the non-operated shoulders. Results: All animals recovered and resumed normal cage activity. All X-rays demonstrated correct implant positioning except for one in which the implant was displaced. Histologic evaluation demonstrated arthritic changes in the implanted shoulder. Decreased Trabecular thickness and Trabecular Spacing were documented among the implanted parties ( p < .05). Bone Mineral Density and Tissue Mineral Density were reduced in the operated shoulder although not significantly ( p = .07). Conclusions: This study demonstrated significant glenoid cartilage wearing in the operated shoulder. Furthermore, the presence of an intra-articular hemiarthroplasty implant diminished underlying glenoid bone quality. This novel, in vivo -model will enable researchers to test implant materials and their effects on cartilage and bone tissue in a cost-effective reproducible rat model.